Development of a Peanut Shell-Derived Chitosan–Activated Carbon Composite as a Sustainable Adsorbent for Permanganate (MnO₄⁻) Removal from Aqueous Solution - Sembiring, Junita Br; Sylvia, Diana; Pohan, Maya Sari Ananda (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The presence of permanganate (MnO₄⁻) in aqueous environments is an emerging environmental concern, as elevated concentrations may compromise aquatic ecosystems and water quality. Converting agricultural biomass into adsorbent materials offers a promising and sustainable route for addressing this issue. This study introduces a novel glutaraldehyde-crosslinked chitosan–activated carbon composite synthesized from peanut shell waste for removing permanganate ions under acidic conditions. Peanut shell biomass was first carbonized and then chemically activated with phosphoric acid to obtain activated carbon, which was subsequently blended with a chitosan solution through ionic gelation and stabilized by glutaraldehyde crosslinking. Functional group changes in the resulting composite were characterized by Fourier Transform Infrared (FTIR) spectroscopy, while its permanganate-removal performance was assessed through batch adsorption trials at pH 3, with residual concentrations measured spectrophotometrically using a calibration curve exhibiting excellent linearity (R² = 0.996). The FTIR spectra displayed noticeable shifts in absorption bands, confirming interaction between the functional groups of chitosan and activated carbon. Removal efficiencies of 93.48% and 91.60% were obtained for initial permanganate concentrations of 25 and 30 mg L⁻¹, equivalent to adsorption capacities of 5.84 and 6.87 mg g⁻¹, reflecting the synergistic role of the porous carbon framework and the amino/hydroxyl groups of chitosan as active binding sites. These findings confirm that peanut shell waste can be valorized into an effective, low-cost, and environmentally friendly adsorbent for permanganate remediation in water treatment.